Speaking Practice using ChatGPT’s Voice Conversation: A Review on Potentials and Concerns - Pratiwi, Novita; Efendy, A. Gusti; Rini, Happy Cruzia; Ahmed, Nagy Abdelraouf (Journal of Language Intelligence and Culture, 2024)
Investigating the pedagogical potentials and concerns of ChatGPT's voice conversation feature within the context of language learning, this study begins by exploring the historical context and limitations of traditional language learning methods, such as language exchange, conversation classes, and role-plays. The discussion then shifts to the rise of AI in education, highlighting ChatGPT's advanced capabilities in providing personalized, interactive, and efficient language instruction through natural language processing, machine learning, and speech recognition. While offering advantages such as accessibility, adaptability, and personalized feedback, the technology also presents limitations in accurately assessing pronunciation and contextual nuances. To effectively integrate ChatGPT into language instruction, educators must carefully consider its strengths and weaknesses. This research explores those things to optimize their use and ensure they complement, rather than replace, traditional language teaching methods.